Effectiveness of motivational videos for elite swimmers: Subjective and biological evaluations - Hagiwara, G.; Akiyama, D.; Tsunokawa, T.; Mankyu, H. (Journal of Human Sport & Exercise, 2019)
Motivational videos (MVs) are used in Japan in many competitive sports, both professional and amateur. However, several researchers have stated that the effectiveness of MVs has not been scientifically verified, and only subjective evaluations have been conducted in previous studies (Yamazaki & Sugiyama, 2009). This study examined the psychological effectiveness of MVs using both subjective and biological evaluations. The subjects were six elite Japanese collegiate swimmers participating in the FINA Swimming World Cup (age: 21.33 ± 0.51, four males and two females). We employed subjective and biological evaluations to examine these elite swimmers` psychological motivation while watching an MV as part of their practice. We adopted subjective and self-report Psychological Condition Inventory (Yamazaki et al., 2008) to measure the athletes` level of vigor while watching the MV. An electroencephalogram (EEG) was employed to evaluate the emotions of the swimmers. The emotional condition (vigor) was analysed by combining the extracted raw EEG data using a KANSEI module logger (Littlesoftware, 2018). A subjective evaluation showed that the score for vigor significantly improved after watching the MV (t = 2.33, p < 0.05), which was also indicated by the results of the biological evaluation (t = 5.69, p < 0.01). There was also a significant correlation between subjective and biological vigor after watching the MV (r = 0.77, p < 0.01). The results of this study, therefore, indicated that biological evaluation can be employed anew to verify the effectiveness of MVs.